Nutrient fluxes from recent deposits of fine-grained, organic-rich sediments in a Florida estuary - Fox, Austin L.; Trefry, John H. (Frontiers in Marine Science, 2023)
Nutrient fluxes from fine-grained, organic-rich sediments in estuaries can hasten the onset and progression of eutrophication and harmful algal blooms. Targeted efforts to manage degraded sediments and improve estuarine water quality require a better understanding of physicochemical controls and the relative importance of benthic fluxes. Toward that end, we determined fluxes from organic-rich, high porosity sediments deposited during the past 5-6 decades along 60 km of the Indian River Lagoon, a barrier island lagoon in Florida, USA. Highly bioavailable ammonium and phosphate were the predominant chemical forms of interstitial nitrogen and phosphorus in these highly-reducing sediments. Median fluxes of ammonium and phosphate were 320 µmol m -2 h -1 and 11 µmol m -2 h -1 , respectively. Fluxes were 3-10 times greater when sediment temperatures were >28°C and interstitial sulfide concentrations were >1 mM. Temperature-compensated fluxes of ammonium and phosphate were significantly correlated with sediment organic matter content; total organic carbon averaged 5.3 ± 2.4% and the maximum was 12.4% for the sediments studied. Fine-scale physical probing, plus lidar data, showed that these organic-rich sediments covered <10% of our study area; however, fluxes from these sediments were estimated to supply 20-40% of internal + external annual loads of nitrogen and phosphorus. Furthermore, 60% of nitrogen and phosphorus fluxes from sediments in the northern Indian River Lagoon came from just 22% of the total surface area. Lagoon segments with high benthic fluxes overlapped in part with areas prone to harmful algal blooms. Effective strategies to manage degraded sediments in the Indian River Lagoon depend on knowing the relative magnitude of internal loading of nutrients as well as appropriate techniques to mitigate sediment fluxes.